1998
DOI: 10.1161/01.res.83.7.697
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Axl Tyrosine Kinase After Vascular Injury and Regulation by G Protein–Coupled Receptor Agonists in Rats

Abstract: Axl is a receptor tyrosine kinase originally identified as a transforming gene product in human myeloid leukemia cells. Cultured rat vascular smooth muscle cells also express Axl, where it has been proposed that Axl may play a role in cell proliferation. In the current study, we tested the hypotheses that Axl expression would parallel neointima formation in balloon-injured rat carotid, and that Axl expression would be regulated by growth factors present at sites of vascular injury. Ribonuclease protection assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(143 citation statements)
references
References 25 publications
(35 reference statements)
4
137
0
Order By: Relevance
“…Gas6 involvement in tissue repair has been documented in injured rat carotid where Axl and Gas6 expression was related to neointima formation. 12 Another role for Gas6 could be its involvement in clearance of dying cells that is carried out by macrophages and HSC/MFB 42 and precedes regeneration. Recognition of dying cells involves surface receptors on phagocytes and extracellular ligands with binding sites on both damaged cells and phagocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas6 involvement in tissue repair has been documented in injured rat carotid where Axl and Gas6 expression was related to neointima formation. 12 Another role for Gas6 could be its involvement in clearance of dying cells that is carried out by macrophages and HSC/MFB 42 and precedes regeneration. Recognition of dying cells involves surface receptors on phagocytes and extracellular ligands with binding sites on both damaged cells and phagocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Gas6 supports haematopoietic stem cell growth 6 and promotes fibroblast and endothelial cell survival. [7][8][9] Gas6/Axl signaling induces accumulation of mesangial cells in kidney fibrosis, 10,11 vascular smooth muscle cells in response to intimal vascular injury, 12 and cardiac fibroblasts 9 during the wound healing process. Thus, this pathway has been increasingly implicated in growth and survival processes during development, regeneration, and tissue repair.…”
mentioning
confidence: 99%
“…Cells and Transfection-VSMC were obtained from rat aorta as described (36). HEK293 cells and VSMC were cultured in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum, penicillin, and streptomycin at 37°C in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…7,11 ProS/TAM interactions may play a role in vascular function, because ProS and TAM receptors are expressed by ECs, 14,18 pericytes, 19 and vascular smooth muscle cells. 20 Recently, using tissue-specific conditional PROS1 knockout mice, it was demonstrated that extrahepatic ProS represents ϳ 45% of normal circulating ProS and that much of this residual ProS is produced by ECs. 4 ECs play key roles in many processes, among which angiogenesis is a major one.…”
Section: Introductionmentioning
confidence: 99%